How Cooperation between Archaeologists and Art Conservators helps us discover more Information: Archaeological Investigations at the Jewish Cemetery on Okopowa Street in Warsaw - Magdalena Sugalska (Fasciculi Archaeologiae Historicae, 2023)
The article concerns archaeological research in plot 1 at the Jewish cemetery at 49/51 Okopowa Street in Warsaw (Wola necropolis). Thanks to simultaneous archaeological works and tombstone conservation, it is possible to examine the underground parts of the matzevot. Archaeologists present at the removal of matzevot for conservation have the opportunity to document the profiles of burial pits created during the demolition of tombstones. The information obtained in this way is very valuable in reconstructing the ways in which tombstones were made and decorated. Traces of polychromies are often preserved in the lower part of the matzevot covered with soil. Such observations are not possible during archaeological research, which is carried out at shallow depths, as recommended by the Rabbinical Commission for Jewish Cemeteries in Poland.